Universe (Chicago Encyclopaedia Britannica, 2011)
Updated for 2011, the Universe, is one book in the Britannica Illustrated Science Library Series that covers today's most popular science topics, from digital TV to microchips to touchscreens and beyond. Perennial subjects in earth science, life science, and physical science are all explored in detail. Amazing graphics-more than 1,000 per title-combined with concise summaries help students understand complex Read more
The world around us (outer space)
1 2 5 8 12 13 15 17 18 20 21 22
NEW_ZTN_GN
Keywords: Astronomy -- Juvenile literature; Astronomy; Outer space -- Exploration